A review on trends in microencapsulation of bioactive compounds: coating materials, design, and applications - Saadi, Sami; Nacer, Nor Elhouda; Chenaker, Hichem; Ariffin, Abdul Azis; Ghazali, Hasanah Mohd; Saari, Nazamid; Mohammed, Abdulkarim Sabo; Anwar, Farooq; Hamid, Azizah Abdul (Springer, 2023)
Encapsulation of bioactive compound has some encountered issues associated particularly to their mode of fabrication, design, and biodegradability. For these reasons, selecting appropriate coating materials like hydroxyl cellulose has several advantages such as modification of moisture, crystal growth, and viscosity. In addition, starches, maltodextrins, whey proteins, chitosan, zein/pectin, and alginates are considered an important coating materials used during microencapsulation processing steps. Thus, the variability in the hydrophilicity, lipophilicity and chargeability levels of those coating materials along with the encapsulation is considered among the molecular aspects in forming genius emulsion vesicles, microgels, solid lipid nanoparticles, liposomes, or core shell nanoparticles. These encapsulation designs are capable in promoting variable physicochemical and therapeutic features such as intra-atomic dimensions, dispersed volumes, release kinetics, and stability levels. Under these desired structural and molecular parameters, in addition to proper optimization of processing conditions, perfect microcarriers and microcapsules could be achieved. Moreover, appropriate control of copolymerization and crystallization of the coating materials with some antagonistic pharmaceutical drugs needs special emphasize. In general, this manuscript reviews various important aspects of structured materials used along with their production and potential uses for enhancing targeted delivery and release of therapeutic foods.